2014
DOI: 10.1111/anu.12102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary lipid sources on growth, reproductive performance and fatty acid compositions of muscle and egg in three-spot gourami (Trichopodus trichopterus) (Pallas, 1770)

Abstract: Five isonitrogenous (420 g kg−1 crude protein) and isoenergetic (16.3 kJ g−1) practical diets were formulated to contain fish oil (FO), Kilka fish oil (KFO), linseed (LO), canola (CO) and soybean (SBO) oils fed to juveniles of three‐spot gourami (Trichopodus trichopterus) (initial weight 1 ± 0.03 g) three times per day to apparent satiation for 14 weeks. Results showed the mean final weight of brooders was not significantly affected by dietary oil sources. Specific growth rate for fish fed in SBO and CO diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…In the current study, the time required for sexual maturity in female three-spot gourami was recorded between 81 and 98 days after stocking, which is comparable with 80-85 days in the same species in a previous work (Seifi Berenjestanaki et al 2014). McKinnon and Liley (1987) and Reyes-Bustamante and Ortega-Salas (2002) reported that T. trichopterus reached a maximum length of 15-20 cm and sexual maturity took place at a length of 7 cm and ages of 12-14 weeks.…”
Section: Reproductive Performancesupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, the time required for sexual maturity in female three-spot gourami was recorded between 81 and 98 days after stocking, which is comparable with 80-85 days in the same species in a previous work (Seifi Berenjestanaki et al 2014). McKinnon and Liley (1987) and Reyes-Bustamante and Ortega-Salas (2002) reported that T. trichopterus reached a maximum length of 15-20 cm and sexual maturity took place at a length of 7 cm and ages of 12-14 weeks.…”
Section: Reproductive Performancesupporting
confidence: 88%
“…In a recent study by Seifi Berenjestanaki et al (2014), lower GSIs (6.77-11.97 %) were obtained in the same species. The different GSI values estimated in the two studies may be due to differing feeding frequencies and rates (four times per day in this study).…”
Section: Reproductive Performancementioning
confidence: 78%
“…There are few studies about the effect of FO replacement by SO on reproductive performances of fish (El‐Sayed et al, ; Jaya‐Ram et al, ; Quintero et al, ; Seifi Berenjestanaki et al, ). In pearl gourami fed SO diet mainly due to the high content of linoleic acid (18:2n‐6) and the lack of n‐3 LC‐PUFA such as EPA and DHA, reproductive performances were decreased as previously reported (El‐Sayed et al, ; Quintero et al, ; Seifi Berenjestanaki et al, ). The possible reason is that fish fed SO diet was not able to biosynthesis n‐3 LC‐PUFA as we can see from the results of fatty acids and probably many pathways such as vitellogenesis, prostaglandin synthesis and steroid metabolism were negatively affected (Tocher, ; Wathes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid level is dependent on dietary lipid content and quality. Vegetable oils had been reported to show a positive effect on anabantids (Berenjestanaki et al, ). In the present study, groundnut oil was blended with crude sardine oil at a 1:1 ratio and used in the experimental diets.…”
Section: Discussionmentioning
confidence: 99%
“…Zuanon et al () indicated that 37% dietary protein was necessary for Trichogaster lalius. Berenjestanaki, Fereidouni, Ouraji, and Khalili () evaluated the effect of different lipid sources on growth and reproductive performance of the three‐spot gourami, T. trichopterus. They found that fish diets, which contained 12% lipid, in which 50% of the lipid source could be substituted with vegetable oils, particularly canola and linseed, showed improved reproductive performance compared to feeds containing only fish oil as the lipid source.…”
Section: Introductionmentioning
confidence: 99%